Pyrolysis processing of PFAS-impacted biosolids, a pilot study. (3rd April 2022) - Thoma, Eben D.; Wright, Robert S.; George, Ingrid; Krause, Max; Presezzi, Dario; Villa, Valentino; Preston, William; Deshmukh, Parik; Kauppi, Phil; Zemek, Peter G.
ABSTRACT: Concentrations of per- and poly-fluoroalkyl substances (PFAS) present in wastewater treatment biosolids are a growing concern. Pyrolysis is a thermal treatment technology for biosolids that can produce a useful biochar product with reduced levels of PFAS and other contaminants. In August 2020, a limited-scope study investigated target PFAS removal of a commercial pyrolysis system processing biosolid with the analysis of 41 target PFAS compounds in biosolids and biochar performed by two independent laboratories. The concentrations of 21 detected target compounds in the input biosolids ranged between approximately 2 µg/kg and 85 µg/kg. No PFAS compounds were detected in the biochar. The PFAS concentrations in the biochar were assumed to equal the compounds' minimum detection limits (MDLs). The pyrolysis system's target PFAS removal efficiencies (REs) were estimated to range between >81.3% and >99.9% (mean >97.4%) with the lowest REs being associated with the lowest detected PFAS concentrations and the highest MDLs. No information on non-target PFAS compounds in influent or effluent media or products of incomplete combustion was considered. Selected gaseous emissions were measured by Fourier transform infrared spectroscopy and gas chromatography time-of-flight mass spectrometry to provide additional information on air emissions after process controls. This limited-scope study indicated that additional research to further understand this process is warranted. Implications : Development of alternative approaches to manage PFAS-impacted biosolids is of emerging international importance. A commercially operating biosolid pyrolysis process was shown to lower target PFAS levels in produced biochar. Additional research is warranted to understand all potential PFAS transformation emission routes and optimal air pollution emissions control strategies for this technology class.